Double Balloon Cervical Ripening Catheter for Control of Massive Hemorrhage in a Cervical Ectopic Pregnancy - Nabila Zambrano; James Reilly; Michael Moretti; Nisha Lakhi (Hindawi Limited, 2017)
Cervical pregnancy can be complicated by perfuse vaginal bleeding. Mechanical compression directed at tamponing the cervical vessels can control hemostasis. There are several types of balloon catheters that have been described for cervical compression. However use of a double balloon catheter is a novel approach for cervical tamponade, as one balloon is positioned below the external cervical os and the second balloon is situated above in the internal cervical os. This compresses the cervix from internal os to external os between the two balloons, forming a "cervical sandwich." We describe this method of cervical tamponade using a silicone double balloon cervical ripening catheter that rapidly controlled hemorrhage in a patient that failed conservative management with methotrexate.